2015
DOI: 10.1016/j.electacta.2014.12.168
|View full text |Cite
|
Sign up to set email alerts
|

CO-sensing properties of a NASICON-based gas sensor attached with Pt mixed with Bi2O3 as a sensing electrode

Abstract: NASICON (Na 3 Zr 2 Si 2 PO 12 )-based gas sensors capable of detecting various gases (CO 2 , NO 2 , Cl 2 , VOC and so on) have so far been developed by many researchers. In this study, planar-type gas sensors using a NASICON disc attached with Pt mixed with Bi 2 O 3 as a sensing electrode (Pt(nBi 2 O 3 ), n (0.01~30): the amount of Bi 2 O 3 addition (wt%)) and Pt as a reference electrode were fabricated, and their sensing properties to CO and H 2 were examined in the operating temperature range of 25~300ºC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 25 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…17 mV). 9 This result demonstrated that even the addition of 1 wt% Bi 2 O 3 into the Pt SE was quite effective in improving the CO-sensing properties. However, the E values in air of these Pt(nBi 2 O 3 )/Pt sensors shifted to the negative direction after the 1st CO exposure, even though the E value of the Pt(nBi 2 O 3 )/Pt sensors at the the 1st CO exposure was comparable to that at the 2nd CO exposure.…”
Section: ¹1mentioning
confidence: 48%
See 3 more Smart Citations
“…17 mV). 9 This result demonstrated that even the addition of 1 wt% Bi 2 O 3 into the Pt SE was quite effective in improving the CO-sensing properties. However, the E values in air of these Pt(nBi 2 O 3 )/Pt sensors shifted to the negative direction after the 1st CO exposure, even though the E value of the Pt(nBi 2 O 3 )/Pt sensors at the the 1st CO exposure was comparable to that at the 2nd CO exposure.…”
Section: ¹1mentioning
confidence: 48%
“…Bi 2 O 3 powder was synthesized as follows. 9 After Bi(NO 3 ) 3 ·5H 2 O was fully dissolved in HNO 3 aqueous solution, an appropriate amount of polyvinyl pyrrolidone was added to the solution as a stabilizing agent and then they were stirred for 15 min. The resultant solution was slowly and continuously dropped into NaOH solution while stirring, until the pH reached 11.…”
Section: Preparation Of Nasicon and Mo Powdersmentioning
confidence: 99%
See 2 more Smart Citations
“…Takeda et al also reported that an addition of Bi 2 O 3 into a Pt-sensing electrode of a NASICON-based sensor was dramatically improved the CO selectivity against H 2 at RT [22,23]. SnO 2 mixed with CeO 2 and PdO x [24], partially-reduced TiO 2 [25], In-doped ZnO [26], CuO-coated Zn 2 SnO 4 [27] and Pd/SnO 2 nanocomposite mixed with carbon nanotube [28] were utilized as a promising CO-sensing material for semiconductor gas sensors with high CO selectivity against inflammable gases.…”
Section: Introductionmentioning
confidence: 99%